2022
DOI: 10.3390/microorganisms10050987
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Community of the Respiratory Tract of Commercial Chickens and Turkeys

Abstract: Respiratory tract health critically affects the performance of commercial poultry. This report presents data on the microbial community in these organs from a comprehensive study of laying chickens and turkey breeders. The main objective was to characterize and compare the compositions of the respiratory system bacteria isolated from birds of different ages and geographical locations in Poland. Using samples from 28 turkey and 26 chicken flocks, the microbial community was determined by 16S ribosomal RNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…This is consistent with the results of previous studies ( Saati‐Santamaría, et al, 2022 ). Rothia is a frequently detected genus, whereas Leptotrichia is dominant in chicken with low FCR ( Shah, et al, 2019 ; Kursa, et al, 2022 ). Subdoligranulum is a butyrate-producing genus with probiotic activity in chickens ( Polansky, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of previous studies ( Saati‐Santamaría, et al, 2022 ). Rothia is a frequently detected genus, whereas Leptotrichia is dominant in chicken with low FCR ( Shah, et al, 2019 ; Kursa, et al, 2022 ). Subdoligranulum is a butyrate-producing genus with probiotic activity in chickens ( Polansky, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory tract was traditionally thought to be sterile due to the limitations of traditional culture-based microbiology techniques [ 6 8 ]. However, the emergence of culture-independent methods like the next-generation sequencing technology have now provided proof that the avian respiratory tract plays host to a dynamic community of microorganisms, especially bacteria [ 5 , 9 , 10 ]. The resident microbiota of the respiratory tract plays several pathophysiological roles related to pathogen exclusion and enhancing immunocompetence [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a few studies have provided baseline information on the poultry respiratory microbiota [ 9 , 13 ], it is important to synthesize available information into clear concepts to provide direction on the role of respiratory tract commensals and pathogens, as well as well as their relationships to health or disease outcomes in poultry. Accordingly, this review seeks to provide a comprehensive overview on poultry respiratory tract microbiota community structure, factors influencing the community structure, challenges faced in studying this microbiota, and its impact on host health and pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Innate immunity is the first line of defence against microbial infections ( Kursa et al, 2022 ). Bacterial pneumonia is a leading cause of mortality in poultry ( Dreyfuss and Ricard, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that diseases caused by E. coli infections are a severe problem in poultry farming. E. coli is a resident bacterium in poultry and a Gram-negative bacterium whose lipopolysaccharide ( LPS ) in the cell wall membrane is the primary substance that stimulates the host immune response and causes multitissue damage ( Kim et al, 2020 ; Kursa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%